2020
DOI: 10.3390/ma13214846
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 3D and 2D FE Frictional Heating Models for Long and Variable Applications of Railway Tread Brake

Abstract: The article proposes two 3D and 2D numerical FE models of frictional heating for the estimation of temperature distributions in railway tread brake in 1xBg configuration during repeated long-term braking. The results of computations were compared with the time courses of temperature measured using thermocouples throughout the duration of the tests on a full-scale dynamometer for two different brake shoe materials in combination with a steel wheel. The resulting temperature distributions calculated using the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Such finite elements generated the most accurate results without the need to use an extremely fine mesh in the area of high temperature gradients. An experience in the construction of a finite element grid was obtained from previously conducted simulations of heat generation in disc brakes [ 25 ] and tread brakes (wheel-rail) of railway vehicles [ 26 ]. It was found that the linear finite elements significantly falsify the calculations (over 20%) even at many times higher than the default mesh density.…”
Section: Heating With Subsequent Cooling Of the Clutch Elements (Seco...mentioning
confidence: 99%
“…Such finite elements generated the most accurate results without the need to use an extremely fine mesh in the area of high temperature gradients. An experience in the construction of a finite element grid was obtained from previously conducted simulations of heat generation in disc brakes [ 25 ] and tread brakes (wheel-rail) of railway vehicles [ 26 ]. It was found that the linear finite elements significantly falsify the calculations (over 20%) even at many times higher than the default mesh density.…”
Section: Heating With Subsequent Cooling Of the Clutch Elements (Seco...mentioning
confidence: 99%
“…The above compositions of the mixtures have already been used in the stand tests for the 1xBg braking system. The papers [18,22] contain extended information on their material, and tribological and mechanical characteristics. The bench test on a full-scale inertia dynamometer was carried out at the Railway Institute in Warsaw (Fig.…”
Section: Experimental Studies Of Temperature Distribution In a Railwa...mentioning
confidence: 99%
“…During long-lasting and repeated braking, the treads of railway wheels are subjected to complex mechanical and thermal loads [18]. In order to prevent excessive damage to the brake system components, in particular the wheel, it is important to understand the mechanisms and operating conditions that increase the undesirable processes that affect these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…So far, various 3D FE models of frictional heating in friction elements that account for their complicated geometry have been proposed and examined [ 11 , 12 , 13 , 14 , 15 ]. A comparative numerical analysis of temperature in the solid and ventilated railway brake discs is presented in the study [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To remedy this, the temperature changes in the circumferential direction can be ignored in the formulation of the problems, obtaining the axisymmetric 2D models. A comparison analysis of the three- and two-dimensional FE frictional heating models has been conducted for a railway tread brake in the study [ 13 ]. It has been proven that an axisymmetric 2D model can be almost as efficient as a 3D model to estimate the temperature distribution during repeated long-term braking mode.…”
Section: Introductionmentioning
confidence: 99%